2021
DOI: 10.4103/ija.ija_553_21
|View full text |Cite
|
Sign up to set email alerts
|

A study to evaluate the change in perfusion index as an indicator of successful ultrasound-guided supraclavicular block

Abstract: Background and Aims: Perfusion index (PI) is a new simple, objective and non-invasive method for evaluation of the success of central neuraxial and peripheral nerve blocks. So, we conducted a study with an aim to evaluate PI as an indicator for success of ultrasound-guided supraclavicular block (SCB). Methods: 65 patients of either sex, age 18–60 years, American Society of Anesthesiologists physical status I and II posted for upper limb surgery under ultrasound (US)-gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Lal et al . [ 10 ] demonstrated that the mean PI is an objective and faster indicator for evaluating the success of USG-guided SCB. In the present study, the mean PI in the little finger was significantly less than the mean PI in the middle finger and thumb of the anaesthetised hand at 5, 10 and 15 min in the intertruncal group and at 5, 10, 15 and 20 min in the corner-pocket group.…”
Section: Discussionmentioning
confidence: 99%
“…Lal et al . [ 10 ] demonstrated that the mean PI is an objective and faster indicator for evaluating the success of USG-guided SCB. In the present study, the mean PI in the little finger was significantly less than the mean PI in the middle finger and thumb of the anaesthetised hand at 5, 10 and 15 min in the intertruncal group and at 5, 10, 15 and 20 min in the corner-pocket group.…”
Section: Discussionmentioning
confidence: 99%
“…This volumetric change reflects on the AC amplitude (pulsatile) of the measurements. However, more than 90% of the PPG signals are from the quasi-DC portion (non-pulsatile) of the measurements [2].…”
Section: Introductionmentioning
confidence: 99%
“…The resolution or regression of the block occurs first in motor fibers, sensory, and then sympathetic [ 7 ]. A successful PNB changes the blood flow and vascular tone as a consequence of the sympathetic block [ 8 ]. The PI value represents the ratio of pulsatile and non-pulsatile blood flow in peripheral tissue, which is measured by pulse oximetry.…”
Section: Introductionmentioning
confidence: 99%